Pegadaian Syariah di Tengah Digitalisasi: Peluang dan Tantangan - Findiani, Firnanda; Fadilah, Nurul; A, Fira Juni; Latifah, Fitri Nur (WELFARE: Journal of Islamic Economics and Finance, 2025)
As digitalization develops in Indonesia, Pegadaian Syariah is undergoing significant transformation. This study investigates the opportunities and challenges of Pegadaian Syariah in maintaining sharia principles and enhancing financial inclusion through digital innovation. Low digital literacy in the community, regulatory constraints, and competition with conventional financial institutions are the main challenges. These constraints limit the effectiveness of using services, such as the digital Pegadaian Syariah application, which is designed to make transactions easier. Digitalization, this opens up great opportunities, such as expanding services to remote areas, increasing operational efficiency, and supporting the empowerment of small and medium enterprises (MSMEs) through productive financing. Pegadaian Syariah can increase public trust and knowledge about sharia-based services by implementing cross-sector collaborative strategies and digital education. The descriptive method is used in this research to provide a comprehensive overview of how Pegadaian Syariah has been adapted to the current times. By optimally utilizing current technology, Pegadaian Syariah has the opportunity to become a pioneer in the digitalization of Islamic finance in Indonesia.